Effleurage Massage Memberikan Efek Terhadap Intensitas Nyeri Dismenorea Primer - Jamhariyah, Jamhariyah; Karnasih, IGA; Diaz Casitadewi, Della Adelia (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2021)
Dysmenorrhea is a menstrual disorder characterized by lower abdominal pain and even back pain that is often experienced by young women. This is due to increased levels of prostaglandins, causing the uterus to contract. One way that can be done with non-pharmacological therapy, namely effleurage massage (massage). This study aims to analyze the effectiveness of effleurage massage on the intensity of primary dysmenorrhea pain. One Group Pretest-Postest research design with a sample of 22 respondents who experienced primary dysmenorrhea. The instruments used were SOP effleurage massage and observation sheets with Numeric Rating Scale (NRS). The results of the analysis with the Wilcoxon test showed that there were differences in the level of pain intensity of dysmenorrhea before and after it was given (p-value <0.001). Effleurage massage provides an effect in the form of reducing pain by modulating the pain that arises by breaking pain receptors into relaxation and encouraging the release of endorphins. Effleurage massage can be used as a way to reduce the pain of dysmenorrhea because it is proven to be easy, effective, free of cost, and without side effects. Keywords: Effleurage massage, Primary Dysmenorrhea, Pain Intensity